Pembuatan Sistem Administrasi Berbasis Web Pada Kelompok Nelayan Doa Mandeh Pasir Sigadondong desa marunggi Kota Pariaman - januardi nasir januardi; Yasha Langitta Setawan (Pengelola Jurnal Politeknik Negeri Ketapang, 2021)
Pariaman City is located on the west coast of West Sumatra with an area of ​​73.36 square kilometers, consisting of an ocean area of ​​12 square kilometers and a coastline of 12 kilometers. As an area close to the sea, the life of the people of Kota Pariaman is very dependent on marine products. One of the villages in Pariaman City that is very dependent on marine products is the community of Pasir Marunggi Village, South Pariaman District. The strategic location of Pasir Marunggi village is the road to Minangkabau International Airport. The catch is sold on the beach and at auction. From 2000 to 2015 the fishermen's life of Pasir Marunggi village began to develop along with the emergence of technology and the business of rice stalls (restaurants) as one of the tourist attractions in Pariaman City. Some of the obstacles faced in addition to the lack of knowledge in the field of Information Technology in computer-based administrative processes, resulted in undocumented catches and good fisherman cultivation. Thus, the introduction of a computer-based administration system in Marunggi village is very much needed by the surrounding community, especially members of the Joint Business Group (KNM). The service material has been given well and it can be seen that there is an increase in participants' knowledge based on the results of the evaluation that has been done. The average service success rate reaches 77% as measured by participant observations during the activity